Kontribusi Pengalaman Mengajar, Kompetensi Profesional, dan Kompetensi Pedagogik Terhadap Kepemimpinan dalam Pembelajaran Sekolah Dasar - Dwi Semi Sayekti; Supriyoko Supriyoko; Yuli Prihatni (Universitas Sarjanawiyata Tamansiswa, 2022)
The educators can lead students from several angles, one of them is from behind, in accordance with the leadership trilogy of Tut Wuri Handayani. There are several factors that contribute to this, including teaching experience, professional competence, and pedagogical competence. The purpose of this study was to determine the contribution of teaching experience, professional competence, and pedagogical competence to the leadership of Tut Wuri Handayani in the teaching of elementary school teachers in Tempuran Districts simultaneously and partially. This research is quantitative research. The population in this study were 246 elementary school teachers in Tempuran district, Magelang, and the sample of this study was only taken by 50 respondents of elementary school teachers in Tempuran district, Magelang District who used the Issac & Michael formula. To analyze the research data using multiple linear regression analysis and partial correlation. The variable teaching experience, professional competence, and pedagogical competence simultaneously have a significant positive effect on tut wuri handayani leadership in learning for elementary school teachers in Tempuran District, Magelang. The partial test results of variable X1 have no significant positive effect on the variable Y, variable X2 has no significant positive effect on the variable Y and variable X3 has a significantly positive effect on the variable Y. The shape of the effect is positive that there is a tendency that is directly proportional between the independent variables with respect to the dependent variable.